The Parathyroid Hormone-Related Protein/Parathyroid Hormone 1 Receptor Axis in Adipose Tissue - Adriana Izquierdo-Lahuerta (MDPI AG, 2021)
Adipose tissue is an organ that shows great plasticity and is able to adapt to the conditions to which the body is subdued. It participates in the regulation of energetic homeostasis and has endocrine functions. Recent studies have shown how the parathyroid hormone-related protein (PTHrP)/Parathyroid Hormone Receptor 1 (PTH1R) axis participates in the regulation of adipogenesis, opposing the action of Peroxisome proliferator-activated receptor gamma (PPARγ). In addition to this, PTHrP is overexpressed in adipose tissue in situations of wear and tear of the body, favoring browning and lipolysis in this tissue. It is also overexpressed in adipose tissue in stressful situations but in the opposite direction, in obesity, metabolic syndrome, type 2 diabetes mellitus (T2DM) and gestational diabetes mellitus (GDM). In conclusion, the PTHrP/PTH1R axis has a main role in adipose tissue, participating in its differentiation and remodeling. PTHrP might be used in obesity treatment and its complications for its ability to reprogram adipogenesis and adipose tissue expansion, WAT browning and for the improvement of the insulin sensitivity. In addition, PTHrP could even be used as a marker of placental status and maternal adaptations to prevent future metabolic problems in mothers and children, as well as in the treatment of bone-related diseases such as osteoporosis.